Application of Organic Inhibitors to the Corrosion of Materials AISI 1070 Steel - Destri Muliastri; Devi Eka Septiyani; Naufal Afif; Vania Tingting Sirenden; Januar Nur Rohmah Suprihartini (Jurnal Internasional Penelitian Teknologi Terapan, 2021)
AISI 1070 steel is a material that has corrosion when it reacts with the environment. One way to inhibit the corrosion rate is by using organic inhibitors. The organic inhibitors used mango leaves and mango rinds with variations in the concentration of organic inhibitors of 0%, 6%, and 8%, respectively. This study aimed to determine the effectiveness of mango leaf extract and mango rinds as an inhibitor against the corrosion rate of AISI 1070 Steel. The extraction was carried out using the Maceration Method. Fourier Transform Infrared (FTIR), Potenzyodinamic, and Weight Loss tests were carried out in this study. FTIR results show that both mango rinds and mango leaf have ingredients that were able to inhibit the corrosion rate, such as flavonoid functional groups including C – H, C = O, and C – O. Using the weight-loss method, the best corrosion rate was found in the mango rinds extract with a concentration of 8 mL, which was 31.784 mm/year with an inhibition efficiency of 92%. The highest corrosion rate was in 2M H2SO4 solution using potentiodynamic, without a mixture of inhibitors, that is 0.15589478 mm/year.